Nest-site selection, reproductive ecology and shifts within core-use areas of Black-necked Cranes at the northern limit of the Tibetan Plateau - Lixun Zhang; Bei An; Meilin Shu; Xiaojun Yang (PeerJ, 2017)
We investigated population dynamics, breeding pairs, breeding habitat selection, nest density, distance between neighboring nests, nest survival, reproductive success, and recruitment rate for Black-necked Cranes (BNC, Grus nigricollis) during 2013–2015 in Yanchiwan National Nature Reserve (YCW), Gansu, China. Numbers of BNC and breeding pairs remained relatively stable at around 140 individuals and 40 pairs. Recruitment rates ranged from 15.7% to 25.8%. The average nest distance was 718.66 ± 430.50 m (2013), 1064.51 ± 323.99 m (2014) and 534.99 ± 195.45 m (2015). Average nest survival rate, hatching success, and breeding success of all 29 nests were 65.56 ± 5.09%, 57.04 ± 6.12% and 32.78% ± 2.55. Water depth, water body area, and distance to land were positively related to nest survival, while disturbance level showed a negative relationship. However, nest site selection of BNC was determined by habitat type, disturbance and water depth. BNC often foraged in mudflats and freshwater marsh but seldom foraged in saline-alkali wet meadows due to food density and quantity in April, the month when BNC choose nest sites. Conservation strategies based on habitats should consider ecological factors that may not be well predicted by nest site selection. Shifts within core-use areas from satellite tracking of BNC demonstrated that maintaining populations demands that conservation areas are large enough to permit breeding BNC changes in space use. Our results are important for conservation management and provide quantitative reproductive data for this species.